The biological control of malaria mosquito larvae using smaller indigenous freshwater fish species - Theron, Dirk Leopold (University of Limpopo, 1987)
Refer to the document
Thesis (M. Sc.(Microbiology)) -- University of the North, 1987
Keywords: Malaria control; Malaria -- Prevention